Impact of Adjusting for the Reciprocal Relationship Between Maternal Weight and Free Thyroxine During Early Pregnancy - Haddow, James E. (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Among euthyroid pregnant women in a large clinical trial, free thyroxine (FT4) measurements below the 2.5th centile were associated with a 17 lb higher weight (2.9 kg/m(2)) than in the overall study population. We explore this relationship further. METHODS: Among 9351 women with second trimester thyrotropin (TSH) measurements between 1st and 98th centiles, we examine: (i) the weight/FT4 relationship; (ii) percentages of women in three weight categories at each FT4 decile; (iii) FT4 concentrations in three weight categories at each TSH decile; and (iv) impact of adjusting FT4 for weight—in the reference group and in 190 additional women with elevated TSH measurements. RESULTS: FT4 values decrease steadily as weight increases (p<0.0001 by ANOVA) among women in the reference group (TSH 0.05–3.8 IU/L). TSH follows no consistent pattern with weight. When stratified into weight tertiles, 48% of women at the lowest FT4 decile are heavy; the percentage decreases steadily to 22% at the highest FT4 decile. Median FT4 is lowest in heaviest women regardless of the TSH level. In the reference group, weight adjustment reduces overall variance by 2.9%. Fewer FT4 measurements are at either extreme (below the 5th FT4 centile: 4.8% before adjustment, 4.7% after adjustment; above the 95th FT4 centile: 5.0% and 4.7%, respectively). Adjustment places more light weight women and fewer heavy women below the 5th FT4 centile; the converse above the 95th centile. Between TSH 3.8 and 5 IU/L, the FT4 percentage below the 5th FT4 centile is not elevated (3.8% before adjustment, 3.1% after adjustment). Percentage of FT4 values above the 95th centile, however, is lower (1.5% before adjustment, 0.8% after adjustment). Above TSH 5 IU/L, 25% of women have FT4 values below the 5th FT4 centile; weight adjustment raises this to 30%; no FT4 values remain above the 95th FT4 centile. CONCLUSIONS: During early pregnancy, TSH values are not associated with weight, unlike nonpregnant adults. Lower average FT4 values among heavy women at all TSH deciles partially explain interindividual differences in FT4 reference ranges. The continuous reciprocal relationship between weight and FT4 explains lower FT4 with higher weight. Weight adjustment refines FT4 interpretation.